Quality Control Analysis of Tofu Products at Sari Murni Factory Using SQC and FMEA Methods - Mochamad Abiyyu Bahy; Jenji Gunaedi Argo; Rosali Sembiring Colia (Veteran Economics, Management, & Accounting Review, 2025)
This study analyzes quality control for tofu products at SM Sari Murni Tofu Factory using Statistical Quality Control (SQC) and Failure Mode and Effect Analysis (FMEA) methods. The study aims to evaluate the defect level, identify key causes of defects, and propose improvement measures. The results from SQC indicate that tofu product defects are within not acceptable tolerance limits. This method utilizes statistical tools such as control charts to monitor production process variability, improve efficiency, and reduce costs. Meanwhile, FMEA successfully identified two critical processes, namely cutting and pressing, with the highest Risk Priority Numbers (RPN) of 648 and 504, respectively. These findings highlight the need for improvements, including enhanced machine reliability, operator training, and stricter production process monitoring. The combination of SQC and FMEA proved effective in reducing defect rates, improving product quality, and maintaining market competitiveness. This study provides strategic recommendations for SM Sari Murni Tofu Factory to achieve continuous quality improvement.  Keywords: Quality Control, Statistical Quality Control, Failure Mode and Effect Analysis, Product Defects, Tofu Factory   Abstrak Penelitian ini menganalisis pengendalian kualitas produk tahu di Pabrik Tahu SM Sari Murni dengan menggunakan metode Statistical Quality Control (SQC) dan Failure Mode and Effect Analysis (FMEA). Penelitian ini bertujuan untuk mengevaluasi tingkat kewajaran cacat produk, mengidentifikasi penyebab utama kecacatan, serta memberikan usulan perbaikan. Hasil analisis menggunakan SQC menunjukkan bahwa tingkat kecacatan produk tahu berada dalam batas toleransi yang tidak dapat diterima. Metode ini memanfaatkan alat statistik seperti peta kendali untuk memantau variabilitas proses produksi, meningkatkan efisiensi, dan mengurangi biaya. Sementara itu, FMEA berhasil mengidentifikasi dua proses kritis, yaitu pemotongan dan pengepresan, dengan nilai Risk Priority Number (RPN) tertinggi masing-masing sebesar 648 dan 504. Temuan ini menunjukkan perlunya langkah perbaikan, seperti peningkatan keandalan mesin, pelatihan operator, dan pengawasan yang lebih ketat terhadap proses produksi. Kombinasi penerapan SQC dan FMEA terbukti efektif dalam mengurangi tingkat kecacatan, meningkatkan kualitas produk, serta menjaga daya saing produk tahu di pasar. Penelitian ini memberikan rekomendasi strategis bagi Pabrik Tahu SM Sari Murni dalam meningkatkan kualitas produk secara berkelanjutan.   Kata Kunci: Pengendalian Kualitas, Statistical Quality Control, Failure Mode and Effect Analysis, Kecacatan Produk, Pabrik Tahu